A potential role of galectin-1 in promoting mouse trophoblast stem cell differentiation. (15th July 2018) - You, Jia-Li; Wang, Wei; Tang, Min-Yue; Ye, Ying-Hui; Liu, Ai-Xia; Zhu, Yi-Min
Abstract: Galectin-1 is highly expressed in blastocysts and trophoblast giant cells during implantation, and dysregulated galectin-1 is associated with many pregnancy-related abnormalities. Elevated galectin-1 contributes to cancer cells invasion. Here, we found that galectin-1 is expressed in mouse oocytes, preimplantation embryos (all stages), and trophoblast stem (TS) cells. Peak levels of galectin-1 mRNA and protein were detected on day 4 and day 5 after the induction of TS cells differentiation. Overexpression of galectin-1 increased TS cells migration and invasion, whereas knockdown of galectin-1 attenuated these effects. Additionally, knockdown of galectin-1 in TS cells decreased the expression of matrix metalloproteinase (MMP) 2/9, ZEB-1, Snail, N-cadherin, TGF-β, Nodal, and phospho-Smad2/3, whereas the expression of E-cadherin was increased. In contrast, overexpression of galectin-1 in TS cells increased the expression of MMP2/9, ZEB-1, and N-cadherin, whereas the expression of E-cadherin was decreased. These findings suggest a potential role of galectin-1 in the differentiation of mouse TS cells. Highlights: Galectin-1 is expressed in mouse oocytes, pre-implantation embryos, and TS cells. Peak levels of Galectin-1 were detected on day 4 and day 5 of TS cells differentiation. Overexpression of Galectin-1 increased TS cell migration and invasion. Knockdown of Galectin-1 decreased TS cell migration and invasion. Galectin-1 modulates the expressions of MMPs and EMT/TGF-β-related molecules.